OxyChip Implantation and Subsequent Electron Paramagnetic Resonance Oximetry in Human Tumors Is Safe and Feasible: First Experience in 24 Patients - Schaner, Philip E.; Pettus, Jason R.; Flood, Ann Barry; Williams, Benjamin B.; Jarvis, Lesley A.; Chen, Eunice Y.; Pastel, David A.; Zuurbier, Rebecca A.; diFlorio-Alexander, Roberta M.; Swartz, Harold M.; Kuppusamy, Periannan (Frontiers in Oncology, 2020)
Introduction: Tumor hypoxia confers both a poor prognosis and increased resistance to oncologic therapies, and therefore hypoxia modification during anti-cancer treatment is desirable. The OxyChip is an implantable oxygen sensor that can detect tumor oxygen levels using electron paramagnetic resonance (EPR) oximetry. We report initial safety and feasibility outcomes after OxyChip implantation in a first-in-humans clinical trial (NCT02706197, www.clinicaltrials.gov). Materials and Methods: Twenty-four patients were enrolled. Eligible patients had a tumor ≤ 3 cm from the skin surface with planned surgical resection as part of standard-of-care therapy. After an initial cohort of six patients who received surgery alone, eligibility was expanded to patients receiving either chemotherapy or radiotherapy prior to surgical resection. The OxyChip was implanted into the tumor using an 18G needle; a subset of patients had ultrasound image-guided implantation. EPR oximetry was carried out using a custom-built clinical EPR scanner. Patients were evaluated for associated toxicity immediately after OxyChip placement and during EPR oximetry measurements. The OxyChip was removed during standard-of-care surgery, and pathologic analysis of the tissue surrounding the OxyChip was performed. Results: The majority of patients had a squamous cell carcinoma of the skin (33%) or a breast malignancy (33%). Eighteen patients received surgery alone, while five underwent chemotherapy and one underwent radiotherapy prior to surgery. No unanticipated adverse device events occurred. The maximum severity of any adverse event as graded by the Common Terminology Criteria for Adverse Events v4.0 was 1, and all were related to events typically associated with implantation. After surgical resection, 45% of the patients had no histopathologic findings specifically associated with the OxyChip. All tissue pathology was “anticipated” excepting a patient with greater than expected inflammatory findings, which was assessed to be related to the tumor as opposed to the OxyChip. Based on pathologic and imaging findings, placement within the tumor was achieved with an 80% to 73% success rate, with and without ultrasound imaging, respectively. Conclusion: This report of the first-in-humans trial of OxyChip implantation and EPR oximetry demonstrated no significant clinical pathology or unanticipated adverse device effects. Use of the OxyChip in the clinic was thus safe and feasible.